Development of a parent training module to improve the well being of children with autism - Amelia Inbam Neelagandan; Mohd Dahlan A. Malek (Fakulti Psikologi dan Pendidikan, 2021)
Autism is a neurodevelopmental disorder characterized by deficits in social communication, restricted, repetitive behaviour, interest or activities, and these symptoms limit and impair everyday functioning. Children with autism have been documented to have lower health related quality of life (HRQOL) compared to their typically developing peers and even children with other chronic illnesses. Aim: This is part of a larger study which aims to improve the HRQOL of children with autism in Sabah. The aim of this portion of the study was to develop a Parent Training Module for Parents of Children with Autism. A literature search was conducted on all major search engines with the keywords autism quality of life, autism HRQOL, autism parent training, autism physical, autism emotions, autism social skills, autism school functioning, module development and adult learning principles. Professionals in the field of autism were consulted for suggestions on developing the parent training module. The author also attended a workshop on module development, reliability and validity. The parent training module content was developed based on evidence based methods to improve the HRQOL of children with autism. The structure of the module was based on The resulting module consisted of 5 units; introduction, physical functioning, emotional functioning, social functioning and school functioning. Each unit consists of various activities such as lectures, group discussions and hands on practice. Parents then plan on paper how they will implement these activities at home with their child, and record each activity in a log form, which will be used as a measure of treatment fidelity. The newly developed parent training module has the potential to guide parents to improve the well-being of children with autism.